Monitoring diet composition and quality of ranging goats by faecal NIRS - Glasser T.; Landau S.; Muklada H.; Dvash L.; Perevolotsky A.; Ungar E.D. (Advanced nutrition and feeding strategies to improve sheep and goat, 2007)
The present study tested the ability of faecal NIRS to predict quantitative and qualitative attributes of the diets of goats grazing Mediterranean scrubland in the Carmel mountain ridge of Israel. This landscape is dominated by the shrubs Pistacia lentiscus and Phillyrea latifolia, with interspersed patches of herbaceous vegetation. A group of 12 goats foraged in the study area for four hours daily and were supplemented with 100- 300 g/d of concentrate feed. During two observation days, one randomly-selected focal goat was observed continuously, and the species foraged, the number and size category of bites removed were recorded by dictation into a tape-recorder. Periodically, bites of each selected species and size category were sampled by clipping and collected for estimation of bite weight and quality. Following suitable preparation, faecal samples were scanned by NIRS, and clipped samples were dried, weighed and analysed for chemical attributes by standard procedures. Calibrations were based on 23 pairs of faeces and diets of the observed goats. Equation quality was evaluated by R2 and the standard error of cross validation (SECV). The R2 values obtained for the dietary percentage (on a DM basis) of Pistacia lentiscus, Phillyrea latifolia, CP, ADF, NDF, IVDMD and PEGbinding tannins were 0.88, 0.92, 0.80, 0.93, 0.87, 0.75 and 0.80, respectively. The corresponding SECV values were 6.77, 8.15, 0.81, 1.73, 2.96, 2.44 and 0.97, respectively. The equations for P. lentiscus, P. latifolia and PEG-binding tannins were applied to a set of 83 samples from a previous experiment for external validation. R2 values were 0.78, 0.80, 0.78 and standard error of prediction (SEP) values were 16.78, 13.88 and 2.62, respectively. Results suggest that faecal NIRS can be calibrated under free-grazing conditions but larger calibration datasets will need to be gathered in order to secure the robustness of this technology.
11. Seminar of the FAO-CIHEAM Sub-Network on Sheep and Goat Nutrition, 2005/09/08-10, Catania (Italy)